A Nordic-Baltic perspective on indications for proton therapy with strategies for identification of proper patients. (2nd October 2020) - Brandal, Petter; Bergfeldt, Kjell; Aggerholm-Pedersen, Ninna; Bäckström, Gloria; Kerna, Irina; Gubanski, Michael; Björnlinger, Kirsten; Evensen, Morten E.; Kuddu, Maire; Pettersson, Erik; Brydøy, Marianne; Hellebust, Taran P.; et al.
Abstract: The beneficial effects of protons are primarily based on reduction of low to intermediate radiation dose bath to normal tissue surrounding the radiotherapy target volume. Despite promise for reduced long-term toxicity, the percentage of cancer patients treated with proton therapy remains low. This is probably caused by technical improvements in planning and delivery of photon therapy, and by high cost, low availability and lack of high-level evidence on proton therapy. A number of proton treatment facilities are under construction or have recently opened; there are now two operational Scandinavian proton centres and two more are under construction, thereby eliminating the availability hurdle. Even with the advantageous physical properties of protons, there is still substantial ambiguity and no established criteria related to which patients should receive proton therapy. This topic was discussed in a session at the Nordic Collaborative Workshop on Particle Therapy, held in Uppsala 14–15 November 2019. This paper resumes the Nordic-Baltic perspective on proton therapy indications and discusses strategies to identify patients for proton therapy. As for indications, neoplastic entities, target volume localisation, size, internal motion, age, second cancer predisposition, dose escalation and treatment plan comparison based on the as low as reasonably achievable (ALARA) principle or normal tissue complication probability (NTCP) models were discussed. Importantly, the patient selection process should be integrated into the radiotherapy community and emphasis on collaboration across medical specialties, involvement of key decision makers and knowledge dissemination in general are important factors. An active Nordic-Baltic proton therapy organisation would also serve this purpose.